A Senescence-Centric View of Aging: Implications for Longevity and Disease. Issue 10 (October 2020) - Borghesan, M.; Hoogaars, W.M.H.; Varela-Eirin, M.; Talma, N.; Demaria, M.
Abstract : Cellular senescence is a state of stable cell cycle arrest associated with macromolecular alterations and secretion of proinflammatory cytokines and molecules. From their initial discovery in the 1960s, senescent cells have been hypothesized as potential contributors to the age-associated loss of regenerative potential. Here, we discuss recent evidence that implicates cellular senescence as a central regulatory mechanism of the aging process. We provide a comprehensive overview of age-associated pathologies in which cellular senescence has been implicated. We describe mechanisms by which senescent cells drive aging and diseases, and we discuss updates on exploiting these mechanisms as therapeutic targets. Finally, we critically analyze the use of senotherapeutics and their translation to the clinic, highlighting limitations and suggesting ideas for future applications and developments. Highlights: There is increasing evidence of the detrimental role of senescent cells in aging. Clearance of senescent cells has been shown to improve age-associated pathologies in animal models, leading to promising new clinical trials. Different mechanisms of senescent cells can be exploited pharmacologically to develop new therapeutic targets.